A national survey of individualized pharmaceutical care practice in Chinese hospitals in 2019 - Cai, Mingyuan; Zhou, Liang; Gao, Daihui; Mei, Dan; Zhang, Bo; Zuo, Wei; Yan, Qing (Frontiers in Pharmacology, 2023)
Background Individualized pharmaceutical care, which consists of therapeutic drug monitoring (TDM), pharmacogenetic (PGx) testing and pharmacist-managed clinic (PMC), is one of the most important trends in clinical pharmacy development in the future. While relevant studies in China were primarily single-center or regional. This study aims to explore the current status of individualized pharmaceutical care in China, find out the existing problems and provide references for its further development. Methods An electronic questionnaire was used and national hospitals’ pharmaceutical administration data from January to December, 2019 were collected. The data were sorted into Excel for further statistical analysis. All analyses were descriptive. Results The proportions of hospitals that performed TDM and PGx testing were 12.83% and 9.48%, respectively. The major responsible departments were the clinical laboratory and pharmacy department. External quality control was carried out in around 70% of hospitals for both TDM and PGx testing. More than half of hospitals provided TDM services for valproate sodium, digoxin, carbamazepine, vancomycin and cyclosporine. And an average of 6.84 drugs were performed TDM in 540 hospitals. Clopidogrel and warfarin were the top 2 drugs that performed PGx testing. As for the PMC, 10.03% of hospitals opened PMC, of which 60.00% had independent PMC. Approximately 80% of PMC services were free of charge. Conclusion The development of individualized pharmaceutical care in China is still in the early stage. Different sectors have to coalesce to promote its implementation, including the appropriate education, coverage, reimbursement policies, high-quality evidence, data systems, health system processes and health policies, etc.